Are Danish adolescents' internalizing and externalizing symptoms associated with their substance use?. (30th September 2020) - Vallentin-Holbech, L; Thomsen, K R; Stock, C
Abstract: Background: Several studies have found that externalizing symptoms are associated with harmful substance use. Also, findings suggest that girls are more likely to report internalizing symptoms compared to boys. This study assessed the association between internalizing and externalizing symptoms (independent variables) and substance use and alcohol-related harms (dependent variables). Furthermore, it was investigated whether associations differentiate among boys and girls. Methods: Data from Danish students aged 13-17 years (N = 2601) were collected using online self-administrated questionnaires measuring demographics, substance use (drunkenness, binge drinking, smoking, cannabis use and other illicit drug use) and alcohol-related harms. Externalizing and internalizing symptoms were measured using the Strength and Difficulties Questionnaire. To test associations multilevel logistic regressions were applied for each dependent variable including both internalizing and externalizing symptoms. Gender differences were tested separately. Results: The study population comprised of 1235 boys (47%) and 1366 girls (53%) from 42 schools in the region of Southern Denmark. Strong positive associations between externalizing symptoms and substance use were found for both boys and girls. When internalizing symptoms were present, boys demonstrated a negative association with binge drinking (OR: 0.90, p < 0.001), drunkenness (OR: 0.91, p = 0.001) and alcohol-related harms (OR: 0.91, p = 0.006). Among girls, a negative association was only found for binge drinking (OR: 0.94, p = 0.009). Conclusions: This study demonstrated strong positive associations between externalizing symptoms and substance use both among boys and girls and showed that internalizing problems protect particularly boys from harmful alcohol use. The findings suggest that Danish girls should be considered equally to Danish boys regarding externalizing symptoms and substance use. Key messages: Boys with internalizing problems are more protected against harmful alcohol use compared to girls. Targeting gender-specific risk factors should be considered when developing prevention programmes.